Topic: MyDGB_- Malaysian dairy goat breed - Ahmad Syazni, Kamarudin; Norshida, Ismail; Mohd Nizam, Haron (2018)
MyDGB is a smartphone application which contains the basic information of the breeds on dairy goat commonly farmed in Malaysia. The app was developed to facilitate and enhances the user experience of interaction to identify the goat breed, and learn about the diseases, treatment and others. The idea presented in this paper is to show how MyDGB can be used to enhance the learning experience of students in a ruminant production especially the goat. The MyDGB is a teaching aid supplementing the work of the teacher and students in learning about dairy goat breeds in Malaysia. It purposes is to make the learning process easier, interactive, and fun to experience.